2000
DOI: 10.1007/s007010070088
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Surgical Complications of Intra-Axial Brain Tumours

Abstract: The results from published series concerning surgical complications after craniotomies for brain tumours are not comparable because of the lack of homogeneity between them. The knowledge of the complications rate in each particular neurosurgical department turns out essentially to provide the patient with tailored information about risks before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 48 publications
5
53
2
1
Order By: Relevance
“…This method provides smaller chances of encountering unpleasant surprises in the postoperative period along with better orientation for the surgeon. The rate of postoperative deficit following subcortical tumor ablation in our series has been 12.5%, which is comparable with the 13-27.5% postoperative deficit rates reported in the literature (3,4,21,25). The only postoperative complication encountered in cortical tumor ablation in our series has been a transient motor deficit which spontaneously resolved.…”
Section: Discussionsupporting
confidence: 88%
“…This method provides smaller chances of encountering unpleasant surprises in the postoperative period along with better orientation for the surgeon. The rate of postoperative deficit following subcortical tumor ablation in our series has been 12.5%, which is comparable with the 13-27.5% postoperative deficit rates reported in the literature (3,4,21,25). The only postoperative complication encountered in cortical tumor ablation in our series has been a transient motor deficit which spontaneously resolved.…”
Section: Discussionsupporting
confidence: 88%
“…[19][20][21][22] By using samples from patients who underwent resection of both primary and metastatic tumors, 2 studies associated age with an increased risk of major complications. 7,9 Two other studies, which included only patients who had bone metastases, reported an association between age and increased morbidity and mortality. 19,22 In contrast, 2 studies in patients with malignant glioma concluded that advanced age was not associated with increased morbidity, and no association was observed between age and postsurgical neurologic function.…”
Section: Interpretations In the Context Of The Literaturementioning
confidence: 99%
“…19,22 In contrast, 2 studies in patients with malignant glioma concluded that advanced age was not associated with increased morbidity, and no association was observed between age and postsurgical neurologic function. 20,21 Major limitations of previous study designs included limited assessment of preoperative and intraoperative factors, single-institution patient samples, 7,9,21,22 small sample sizes with few events, 7,21,22 and reliance on univariate analyses to arrive at the conclusions. 7,13,21,22 We identified a greater prevalence for prolonged LOS among elderly patients across our entire sample; however, there was no significant difference between age groups when we examined total hospital LOS as a continuous variable (Table 2).…”
Section: Interpretations In the Context Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations